How much Keynes and how much Schumpeter? An Estimated Macromodel of the US Economy - Guido Cozzi; Beatrice Pataracchia; Philipp Pfeiffer; Ratto Marco (Publications Office of the European Union, 2017)
The macroeconomic experience of the last decade stressed the importance of jointly studying the growth and business cycle fluctuations behavior of the economy. To analyze this issue, we embed a model of Schumpeterian growth into an estimated medium-scale DSGE model. Results from a Bayesian estimation suggest that investment risk premia are a key driver of the slump following the Great Recession. Endogenous innovation dynamics amplifies financial crises and helps explain the slow recovery. Moreover, financial conditions also account for a substantial share of R&D investment dynamics.
Keywords: E3; O3; O4; 330; endogenous growth; R&D; Schumpeterian growth; Bayesian estimation